Attitudes toward Persons with Disabilities and Disability Awareness of University Students Providing Healthcare - Öksüz, Canan Ertemoğlu; Uzun, Özlem Kanber; Kalkışım, Şahi Nur; Zihni, Nihat Burak (UI Scholars Hub, 2023)
Background: This study aims to determine the attitudes and disability awareness of university students who provide health services to persons with disabilities. Methods: This study included 291 volunteer students studying at the Vocational School of Health Services, Karadeniz Technical University (KTU), and conducting clinical practice at KTU Farabi Hospital. A sociodemographic form was used to determine the individual characteristics of the students included in this study, and the Attitudes toward Disabled Persons Scale (ATDP) was applied to determine their attitudes toward persons with disabilities. Results: The students’ average ATDP score was 61.75 ± 12.34. Statistically significant differences were found among situations wherein the students had chronic diseases, participated in disability-related education, and their ATDP scores (p < 0.05). Conclusions: This study shows that our students have few prejudices against persons with disabilities and can empathize with them at a sufficient level. In addition, our students have an awareness of people with disabilities, and this awareness can be increased. Disability-related regulations should be introduced into educational curricula, and additional awareness-raising activities should be provided to improve the attitudes of healthcare students toward persons with disabilities.